Measurement invariance between subjects: what can we learn about subject-related differences in teaching quality? - Wemmer-Rogh, Wida; Grob, Urs; Charalambous, Charalambos Y.; Praetorius, Anna-Katharina (ZDM, 2024)
Recent publications emphasize the need to take greater account of differences in teaching quality between subjects. The empirical analysis of this topic requires a comparison of teaching quality in different subjects to distinguish generic aspects of teaching quality from subject-specific ones. In this paper, we compare teaching quality in mathematics and German lessons using observational data from primary schools in Switzerland ( N Math = 319; N German = 237). Data were collected using an observation instrument reflecting the teaching dimensions of the MAIN-TEACH model, which was developed based on a synthesis of established observation frameworks. The dimensions of classroom management, motivational-emotional support, selection and implementation of content, cognitive activation, support for consolidation, assessment and feedback, and adaptation were tested for subject-related measurement invariance. With a two-fold measurement invariance approach, differences between the subjects were investigated at both a global and an indicator level. When applying alpha accumulation correction, no significant subject-related differences in factor loadings or intercepts were found. The factorial structure of our data was basically identical for the two subjects. The comparison of latent factor means revealed no mean differences between the subjects. We discuss the implications for both the MAIN-TEACH model and research into subject-related differences of teaching in general.